Loss of CD36 protects against diet‐induced obesity but results in impaired muscle stem cell function, delayed muscle regeneration and hepatic steatosis. (1st November 2019) - Verpoorten, Sandrine; Sfyri, Peggy; Scully, David; Mitchell, Robert; Tzimou, Anastasia; Mougios, Vassilis; Patel, Ketan; Matsakas, Antonios
Abstract: Aim: The prevalence of obesity is a major risk factor for cardiovascular and metabolic diseases including impaired skeletal muscle regeneration. Since skeletal muscle regenerative capacity is regulated by satellite cells, we aimed to investigate whether a high‐fat diet impairs satellite cell function and whether this is linked to fatty acid uptake via CD36. We also aimed to determine whether loss of CD36 impacts on muscle redox homeostasis and skeletal muscle regenerative capacity. Methods: We studied the impact of a high‐fat diet and CD36 deficiency on murine skeletal muscle morphology, redox homeostasis, satellite cell function, bioenergetics and lipid accumulation in the liver. We also determined the effect of CD36 deficiency on skeletal muscle regeneration. Results: High‐fat diet increased body weight, intramuscular lipid accumulation and oxidative stress in wild‐type mice that were significantly mitigated in CD36‐deficient mice. High‐fat diet and CD36 deficiency independently attenuated satellite cell function on single fibres and myogenic capacity on primary satellite cells. CD36 deficiency resulted in delayed skeletal muscle regeneration following acute injury with cardiotoxin. CD36‐deficient and wild‐type primary satellite cells had distinct bioenergetic profiles in response to palmitate. High‐fat diet induced hepatic steatosis in both genotypes that was more pronounced in the CD36‐deficient mice. Conclusion: This study demonstrates that CD36 deficiency protects against diet‐induced obesity, intramuscular lipid deposition and oxidative stress but results in impaired muscle satellite cell function, delayed muscle regeneration and hepatic steatosis. CD36 is a key mediator of fatty acid uptake in skeletal muscle, linking obesity with satellite cell function and muscle regeneration.